2022
DOI: 10.3390/en15144934
|View full text |Cite
|
Sign up to set email alerts
|

Developing a Theoretical Framework to Explain the Social Acceptability of Wind Energy

Abstract: The social acceptability of wind farms has been researched for several decades now, with the first research tracing back to the 1980s. This paper aims to deliver a literature review within the structural framework proposed by the paper of variables influencing the acceptability of wind farms. The large amount of research published on the social acceptability of wind farms requires an effort to identify and categorise variables to deliver a holistic understanding of opposition and support to wind energy. We cla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 106 publications
0
4
0
Order By: Relevance
“…Usually, allocation principles are mostly based on merit/desert, equality and need [28]. In the OSW debate, distributive justice is for the most part connected to the possibility of stakeholders receiving a fair share of the benefits coming from the projects implemented referred by Lundheim et al (2022), 'perceived distribution of benefits was an important factor in the acceptance of local wind energy projects' [29]:8. Equally relevant, is the ongoing debate on how and who should be compensated by the negative (environmental and social) impacts that come along with OSW initiatives, both in the present and the future [30].…”
Section: Values and Ethical Principles In Offshore Wind Discoursementioning
confidence: 99%
See 1 more Smart Citation
“…Usually, allocation principles are mostly based on merit/desert, equality and need [28]. In the OSW debate, distributive justice is for the most part connected to the possibility of stakeholders receiving a fair share of the benefits coming from the projects implemented referred by Lundheim et al (2022), 'perceived distribution of benefits was an important factor in the acceptance of local wind energy projects' [29]:8. Equally relevant, is the ongoing debate on how and who should be compensated by the negative (environmental and social) impacts that come along with OSW initiatives, both in the present and the future [30].…”
Section: Values and Ethical Principles In Offshore Wind Discoursementioning
confidence: 99%
“…Such issues inevitably contribute to social (un)acceptance of OSW which can be considered in its several implications of procedural, distributional, and recognition justices, particularly when routinely disadvantaged communities feel the negative effects due to their social disadvantage or minority status [32,33]. In a positive tone, 'good policies could hopefully ensure that affected communities have a sense of justice, regardless of the outcomes' [29]:20.…”
Section: Values and Ethical Principles In Offshore Wind Discoursementioning
confidence: 99%
“…A lack of complete information on these benefits has been shown to foster local social opposition, hindering wind farms' continuous growth (Groth and Vogt 2014;Song et al 2016). Previous studies have indicated that an important factor increasing social opposition to infrastructure projects is the perception of local communities not benefiting from the project and not having been consulted in advance concerning these projects (Hall et al 2013;Lundheim et al 2022). In many situations, energy from the wind is consumed in cities, far away from the installation site.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Rural communities, where wind is installed, may perceive to receive only hardships without benefits (Song et al 2016). For these reasons it is critical to clearly understand and effectively communicate the financial benefits provided by the wind industry to local rural communities (Gross 2007;Copena and Simón 2018;Lundheim et al 2022).…”
Section: Literature Reviewmentioning
confidence: 99%
“…At the same time, the development of new energy sources, energy efficiency and environmental management issues give impetus to the development of science and technology. One of the most promising directions in the development of alternative energy is wind energy [2].…”
Section: Introductionmentioning
confidence: 99%